Central Asia's second chance - Olcott, Martha Brill, 1949- (Carnegie Endowment for International Peace, 2005)
A leading authority on Central Asia offers a sweeping review of the region's path from independence to the post-9/11 world. The first decade of Central Asian independence was disappointing for those who envisioned a straightforward transition from Soviet republics to independent states with market economies and democratic political systems. Leaders excused political failures by pointing to security risks, including the presence of terrorist training camps in Afghanistan. The situation changed dramatically after 9/11, when the camps were largely destroyed and the United States introduced a military presence. More importantly the international community engaged with these states to give them a "second chance" to address social and economic problems. But neither the aid-givers nor the recipients were willing to approach problems in new ways. Now, terrorists groups are once again making their presence felt and some states may be becoming global security risks. This book explores how the region squandered its second chance and what might happen next